2008
DOI: 10.1111/j.1749-7345.2008.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of African Catfish, Clarias gariepinus (Burchell, 1822), to Diets of Pigeon Pea, Cajanus cajan, Subjected to Different Processing Methods

Abstract: Raw undehulled pigeon pea, Cajanus cajan, seeds were processed by toasting, boiling, and soaking before milling to produce pigeon pea meals (PPMs). African catfish, Clarias gariepinus, were fed eight diets formulated with these meals at two dietary inclusion levels of 600 and 650  g/kg in combination with fish waste meal levels of 350 and 330 g/kg, respectively, to yield a protein and energy contents of 35.96  ±  2.1% dry matter and 18.04  ±  0.2 kJ/g. Fish (mean weight 0.46  g) were weighed and distributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…Fermenting process improved crude protein and fat content of AYB while boiling decreased the crude protein and fat content. This is contrary to the report of Ogunji et al (2008b) that most proteins of plant origin are nutritionally improved by heat treatment. Osuigwe et al (2005) observed inferior performance of fish fed boiled Jack Beans Seed Meal (JBSM) relative to those fed the control diet.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Fermenting process improved crude protein and fat content of AYB while boiling decreased the crude protein and fat content. This is contrary to the report of Ogunji et al (2008b) that most proteins of plant origin are nutritionally improved by heat treatment. Osuigwe et al (2005) observed inferior performance of fish fed boiled Jack Beans Seed Meal (JBSM) relative to those fed the control diet.…”
Section: Discussioncontrasting
confidence: 99%
“…ANFs are known to have negative effects on fish growth and general physiology. As such, the removal of ANFs using different processing methods is important to reduce the concentration of those factors (Ogunji et al, 2008b). This strengthens the position of Uwaegbute et al (2012) that quality of foodstuffs may be improved by processing.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Most of these legumes are underutilized and of limited relevance in human nutrition (Osuigwe, 2003). Pigeonpea (Cajanus cajan) seed is one such legume currently underutilized in fish feed production (Ogunji, Osuigwe, Okogwu, & Uwadiegwu, 2008), despite being of good nutritional quality (Elegbede, 1998;FAO, 1982). One possible reason for their underutilization is the presence of anti-nutritional factors (ANFs), such as trypsin inhibitors, haemaglutinin, and saponin (Francis, Makkar, & Becker, 2001;Grimaud, 1988).…”
mentioning
confidence: 99%